2016
DOI: 10.1177/0022034516651077
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of the Ribosome Biogenesis Protein Utp5/WDR43 to Craniofacial Development

Abstract: Fairly recently, it was recognized that human ribosomopathies-developmental defects caused by mutations in ribosome biogenesis proteins-can exhibit tissue-specific defects rather than the expected global defects. This apparent anomaly-that seemingly ubiquitously expressed and required ribosomal proteins can have distinct functions in cell and tissue differentiation-has spurred new areas of research focused on better understanding translational mechanisms, biogenesis, and function in diverse cell types. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…WDR43 can also robustly bind to promoter-associated noncoding/nascent RNA. [ 11 , 30 ] However, several research studies have examined the molecular role of WDR43 up to this point. [ 14 , 25 ] This study conducted an all-encompassing pan-cancer analysis of WDR43 through the entire TCGA cancers to determine its possible functions and underlying pathways through the incidence, proliferation, and clinical outcomes of distinct tumors.…”
Section: Discussionmentioning
confidence: 99%
“…WDR43 can also robustly bind to promoter-associated noncoding/nascent RNA. [ 11 , 30 ] However, several research studies have examined the molecular role of WDR43 up to this point. [ 14 , 25 ] This study conducted an all-encompassing pan-cancer analysis of WDR43 through the entire TCGA cancers to determine its possible functions and underlying pathways through the incidence, proliferation, and clinical outcomes of distinct tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosome biogenesis is a key means to control total protein synthesis and thereby regulate important functions such as cell growth, proliferation, and differentiation. Temporal regulation of ribosome biogenesis, hence protein translation, coordinates specific developmental events in many tissue types (Chau et al, 2018;Sondalle et al, 2016;Trainor and Merrill, 2014). Recent studies with embryonic stem cell derived cardiomyocytes suggest that downregulation of ribosome biogenesis and global protein synthesis are required for cardiomyocyte maturation (Pereira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The WDR43 protein belongs to the protein family containing the WDR domain. It is usually involved in the assembly of small-subunit processome as a conserved component, and mediates the transcription and processing of small-subunit ribosomal RNA (18S rRNA), which plays a key role in the biogenesis of ribosomes [ 8 , 9 ]. Studies have shown that WDR43 can suspend the release of Pol II and promote transcription extension to regulate the high-level transcription and translation process in the pluripotency of embryonic stem cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%